Targeted D4 Dopamine Receptors: Implications for Drug Discovery and Therapeutic Development - Ptacek, Radek; Kuzelova, Hana; B. Stefano, George; Raboch, Jiri; M. Kream, Richard (Current Drug Targets, 2013)
A wealth of preclinical and clinical literature has established functional associations of CNS dopamine (DA) and its multiple G protein-coupled receptor (GPCR) types in the integration of key neurological processes linked to complex behavioral activities. Conversely, an equivalent vast literature supports the role of aberrant CNS DA expression and DA receptor signaling in the etiology and persistence of major psychiatric illnesses and has established selective targeting of DA-ergic systems as a cornerstone of pharmacotherapeutic intervention and current neuroleptic drug development. The present short review focuses on potential functional/behavioral alterations linked to polymorphisms in the primary DNA sequence of the DA receptor type 4 (DRD4) gene in reference to major psychiatric illnesses. The potential clinical relevance of major polymorphisms of the DRD4 gene are discussed within the context of practical aspects of typical and atypical neuroleptic drug usage within afflicted populations of psychiatric patients. It is anticipated that additional complementary molecular, biochemical, and behavioral studies of DRD4 gene polymorphisms will provide essential information for selective targeting of heterogeneous populations of CNS D4 receptors and advance drug discovery and therapeutic development efforts for highly efficacious treatment of psychiatric illnesses.
Keywords: schizophrenia